2015
DOI: 10.1080/0907676x.2014.983530
|View full text |Cite
|
Sign up to set email alerts
|

New trends of Chinese political translation in the age of globalisation

Abstract: This study takes issue with the prescriptive principles of faithfulness and equivalence prevailing in the circle of political translation in China. It argues that the predominant source-oriented view of translation impairs a profound understanding of the intricacies of political translation as an evolving and adaptive practice in the era of globalisation. Selecting English translations of political speeches delivered by Chinese State leaders, we haveidentified sometarget-oriented features.On the basis of a des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…In fact, changes in rendering strategies and textual choices, albeit in a subtle manner, have been perceived in written translations across the time. For instance, Li & Li's (2015) diachronic study of the translations of Chinese political speeches from 1970s to 2010s revealed an increasing number of target-oriented shifts across the span of period, which, as they argued, serve to enhance the level of reception to target readership. In a similar vein, it will be meaningful to inquire into interpreting to see if any changes of comparable shifts can be observed throughout the past decades, since no such investigation has been conducted so far.…”
Section: Takedownmentioning
confidence: 99%
“…In fact, changes in rendering strategies and textual choices, albeit in a subtle manner, have been perceived in written translations across the time. For instance, Li & Li's (2015) diachronic study of the translations of Chinese political speeches from 1970s to 2010s revealed an increasing number of target-oriented shifts across the span of period, which, as they argued, serve to enhance the level of reception to target readership. In a similar vein, it will be meaningful to inquire into interpreting to see if any changes of comparable shifts can be observed throughout the past decades, since no such investigation has been conducted so far.…”
Section: Takedownmentioning
confidence: 99%
“…In other words, mapping conditions and mapping patterns are divergent. Although for a long time, faithfulness and accuracy are the overriding norms in the translation of political texts, while in the era of globalization, there occurs a target-oriented translation shift in Chinese political translation [12]. Therefore, to achieve the intended communicative effects among target readers, domestication can be an effective strategy.…”
Section: B Domesticationmentioning
confidence: 99%
“…For example, (11) 坚持军事斗争准备的龙头地位不动摇, …… [8] Being "action ready" must be its major task … [9] (12) ……坚持以军事斗争准备为龙头带动现代化建 设。 [8] …We should … modernize our armed forces. [9] In examples (11) and (12), "龙头"is an animal metaphor which means being in the core position. The literal equivalent word of "龙"in the west is dragon.…”
Section: Omissionmentioning
confidence: 99%
“…Most of the professional translators in these two organizations are members of the CPC who are followers of the prevailing ideologies pursuing a politically correct translation ethics. In other words, they are required "to integrate their individual knowledge into the institutionalized models and transform the ideological message into textual representation" [4]. It can be observed that ideology not only influences the selection of texts for translation, but also plays as "an invisible hand" [8] to control the production, publication and popularity of the translated texts.…”
Section: A Ideology-influenced Translation Practicementioning
confidence: 99%
“…However, "the traditional view concerning political translation impairs a profound understanding of the intricacy and ideological implications involved in the practice of translating Chinese political discourse" [4]. Consequently, this paper, with the communicative function of political translation in mind, probes into to the communicative translation strategies of Chinese political discourse.…”
Section: Introductionmentioning
confidence: 96%